IMPROVEMENT OF BRAKING PROCESS AT CYCLES OF DRILLING PIPES COLUMN DESCENT - Козак, Федір Васильович; Криштопа, Людмила Іванівна; Лужний, Станіслав Андрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article is devoted to increasing of durability of friction units of a drill hoist due to the improvement of the downhill-lifting unit which greatly affects of technical and economic parameters of drilling. Promising direction of improvement of descent-lifting operations is the automation of braking processes on the basis of the wide introduction of electrical, electronic systems and computer technologies to ensure the optimality of this process, depending on the effect of various factors. Mathematical description of the initial angular velocity of the brake pulley at the beginning of the first stage of braking and the regularity of its angular velocity variation during the whole braking period is made and the number of candles which can be lowered into the well, provided that the internal brake pairs of the permissible temperature for the material of the friction lining are achieved is determined.